(untitled) (2017)
Advances in biomedical engineering (BME) imply the existence of research groups working in multidisciplinary teams to understand physiological processes and develop methods and tools for diagnostics and therapeutics. Multidisciplinary teams include physicians, biologists, physicists, mathematicians and engineers from different disciplines: electrical and electronics, computer sciences, materials, mechanical, chemical, among others. Lately, BME has become a bridge joining these disciplines. Therefore, successful BME projects involve not only a deep knowledge of the specific discipline, but also an understanding of the physiological phenomena under study.